Certain Issues of Applying Self-Defense of Civil Rights (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this scholarly article, the protection of civil rights and legally protected interests is carried out in the manner prescribed by law, that is, through the application of appropriate forms, means and methods of protection.